2017
DOI: 10.7150/thno.18650
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography: Review of Techniques and Clinical Applications

Abstract: Elastography-based imaging techniques have received substantial attention in recent years for non-invasive assessment of tissue mechanical properties. These techniques take advantage of changed soft tissue elasticity in various pathologies to yield qualitative and quantitative information that can be used for diagnostic purposes. Measurements are acquired in specialized imaging modes that can detect tissue stiffness in response to an applied mechanical force (compression or shear wave). Ultrasound-based method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
1,147
1
40

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,303 publications
(1,331 citation statements)
references
References 147 publications
9
1,147
1
40
Order By: Relevance
“…The technique has been described in detail in the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) and World Federation for Ultrasound in Medicine and Biology (WFUMB) guidelines [1,2,4,6,45] and also by others [46]. TE has been used for liver stiffness measurement (LSM) both in children and adults [1,2,47,48].…”
Section: Transient Elastography (Te)mentioning
confidence: 99%
“…The technique has been described in detail in the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) and World Federation for Ultrasound in Medicine and Biology (WFUMB) guidelines [1,2,4,6,45] and also by others [46]. TE has been used for liver stiffness measurement (LSM) both in children and adults [1,2,47,48].…”
Section: Transient Elastography (Te)mentioning
confidence: 99%
“…On the contrary, the smaller the elasticity coefficient is, the larger the morphological change will be. This generalization suggests that deformation of normal soft tissues is much more significant than that of hard tumor tissues [8]. Ultrasonic elastography aims to generate different morphological changes based on differences between the tumor or lesion area and the surrounding normal tissues in terms of the elasticity coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, shear wave elastography (SWE) recently has become available on multiple systems and is attractive due to its 2D imaging capability and quantitative nature. Because of the unique tissue mechanical information provided, numerous clinical studies have demonstrated the clinical utility of ultrasound elastography, such as in liver, breast, prostate, kidney, pancreas, and musculoskeletal (MSK) applications 6, 7, 8, 9, 10, 11. For example, 2D SWE was shown to have high sensitivity in the assessment of liver fibrosis 12.…”
Section: Introductionmentioning
confidence: 99%